Correlation between the Implementation of Excellent Service of Nursing with the Level of Patient Satisfaction in Medika Mulia Hospital of Tuban - Masroyana Masroyana; Suhartono Suhartono; Mokhamad Nurhadi (STKIP Singkawang, 2019)
The purpose of this study was to determine the significance of the correlation between the implementation of excellent services with the level of patient satisfaction. The design of this study used correlational analytics with the Cross-Sectional time approach. The sample in this study was inpatients in the VIP room of Medika Mulia Hospital of Tuban with an accidental sampling technique. The sample size was 56 people. The data collection used a questionnaire instrument. Then analyzed used Spearman Rank statistical test with significance level α = 0.05. The results of study 52 (96.3%) respondents stated excellent service of nursing with a very satisfying level of satisfaction, 2 (3.7%) respondents stated excellent service of nursing with a satisfying level of satisfaction, 1 (50%) stated that nursing service was quite excellent with a level of satisfaction is very satisfied, 1 (50%) of respondents said that the nursing service was excellent with a satisfied level of satisfaction and none of the respondents stated that nursing service was not prime and was not satisfied with the services of nursing. The results of data analysis obtained the value of p = 0.004, meaning p <0.05, which means there was a correlation between the implementation of excellent service of nursing with the level of patient satisfaction in the VIP Room of Medika Mulia Hospital of Tuban.